The “Missing-Part” in Withholding Tax Mechanism - Charoline Cheisviyanny; Herlina Helmy; Nayang Helmayunita; Vanica Serly; Sany Dwita (Pertapsi-Indonesia collaborated with Petra Christian University, 2023)
This research aims to get understanding and find the solution of the problems related to withholding tax mechanism, especially to treasurers and non-treasurers. The informants are the taxpayers who are government partners. Data was collected through interviews and document analysis. The results show the problems are related to the socialization of new policy, the new procurement platform (SIPLah), the harmful mechanism, and the unclear tax rules. The suggested solutions are to strengthen the position of DGT in withholding tax mechanism and to improve inter-ministerial synergy.